Effects of Salvianolic Acid B on Protein Expression in Human Umbilical Vein Endothelial Cells. (14th February 2011) - Chang, Tsong-Min; Shi, Guey-Yueh; Wu, Hua-Lin; Wu, Chieh-Hsi; Su, Yan-Di; Wang, Hui-Lin; Wen, Hsin-Yun; Huang, Huey-Chun
Abstract : Salvianolic acid B (Sal B), a pure water-soluble compound extracted from Radix Salviae miltiorrhizae, has been reported to possess potential cardioprotective efficacy. To identify proteins or pathways by which Sal B might exert its protective activities on the cardiovascular system, two-dimensional gel electrophoresis-based comparative proteomics was performed, and proteins altered in their expression level after Sal B treatment were identified by MALDI-TOF MS/MS. Human umbilical vein endothelial cells (HUVECs) were incubated at Sal B concentrations that can be reached in human plasma by pharmacological intervention. Results indicated that caldesmon, an actin-stabilizing protein, was downregulated in Sal B-exposed HUVECs. Proteins that showed increased expression levels upon Sal B treatment were vimentin, T-complex protein 1, protein disulfide isomerase, tropomyosin alpha, heat shock protein beta-1, UBX domain-containing protein 1, alpha enolase, and peroxiredoxin-2. Additionally, Sal B leads to increased phosphorylation of nucleophosmin in a dose-dependent manner and promotes proliferation of HUVECs. We found that Sal B exhibited a coordinated regulation of enzymes and proteins involved in cytoskeletal reorganization, oxidative stress, and cell growth. Our investigation would provide understanding to the endothelium protection information of Sal B.